A review on inkjet printing of nanoparticle inks for flexible electronics. Issue 29 (15th July 2019) - Nayak, Laxmidhar; Mohanty, Smita; Nayak, Sanjay Kumar; Ramadoss, Ananthakumar
Abstract : The recent progress, challenges and promising future of design and synthesis of inks and device fabrication by inkjet printing are reviewed and discussed. Abstract : Inkjet printing is recognised as an efficient method for direct deposition of functional materials on flexible substrates in predesigned patterns owing to simple processing, low cost and higher adaptability for large scale fabrication of electronic devices, sensors, light emitting diodes, etc. Inks used in inkjet printing mostly consist of organic polymers, metal nanoparticles and carbon materials such as graphene and carbon nanotubes. For effectiveness of the printing process, the fluid dynamic parameters such as viscosity and surface tension, as well as dimensionless quantities such as the Weber number, Reynolds number, and Ohnesorge number, must be within a suitable limit. More frequently, this process suffers due to the formation of a coffee ring during the post printing process, which affects the morphology as well as electrical conductivity of the printed pattern. In this review, we have summarized the various aspects of inks such as fluid dynamical parameters of inks, mechanism of the coffee ring formation, different types of ink preparation strategies and their applications in sensors, thin film transistors, and energy storage devices.